Effect of oral sodium bicarbonate on fibroblast growth factor-23 in patients with chronic kidney disease: a pilot study. Issue 1 (December 2016) - Chen, Wei; Melamed, Michal; Hostetter, Thomas; Bauer, Carolyn; Raff, Amanda; Almudevar, Anthony; Lalonde, Amy; Messing, Susan; Abramowitz, Matthew
Abstract Background The regulation of fibroblast growth factor-23 (FGF23) secretion in patients with chronic kidney disease (CKD) is incompletely understood. Anin vitro study showed that metabolic acidosis increased FGF23 in mouse bone. The objective of this study is to evaluate the effect of oral sodium bicarbonate on circulating FGF23 levels in patients with CKD. Methods This was a single-blind pilot study. Twenty adults with estimated glomerular filtration rate between 15–45 mL/min/1.73 m2 and serum bicarbonate between 20–24 mEq/L were treated with placebo for 2 weeks, followed by increasing doses of oral sodium bicarbonate (0.3, 0.6 and 1.0 mEq/kg/day) in 2 week intervals for a total of 6 weeks. C-terminal FGF23 levels were measured at the initial visit, after 2 weeks of placebo and after 6 weeks of bicarbonate therapy. Wilcoxon matched-pairs signed-rank test was used to compare FGF23 before and after sodium bicarbonate. Results After 6 weeks of oral sodium bicarbonate, the median FGF23 increased significantly from 150.9 RU/mL (IQR 107.7–267.43) to 191.4 RU/mL (IQR 132.6–316.9) (p = 0.048) and this persisted after excluding participants who received activated vitamin D. Conclusions FGF23 increased after short-term oral sodium bicarbonate therapy in patients with CKD and mild metabolic acidosis. It is unclear whether this was due to the alkalinizing effect of sodium bicarbonate or other factors. Trial registration The study was registered at ClinicalTrials.gov (NCT00888290 ) on April 23, 2009.